Gambaran Program Generasi Berencana (GenRe) di Indonesia dan di Provinsi Jawa Timur Tahun 2017 - Ita Mustofa Rini; Yuni Dwi Tjadikijanto (Jurnal Biometrika dan Kependudukan, 2019)
The success of a nation in the future will be largely determined by the quality of adolescents in the present. Therefore, adolescent's personal life must be prepared as early as possible in order to achieve optimal quality. The main program that support the achievement of youth quality is the Generasi Berencana (GenRe) program. This research aims to analyze the description of  GenRe program implementation in Indonesia and in East Java Province based on the 2017 Survey of performance indicators on Population Program, Family Planning and Family Development. This study focuses on increasing age of first marriage, adolescent resproductive health, family development program for adolescent andCounseling Information Centers for Youth. Study found that GenRe program which covers three indicators in both Indonesia and East Java is still unoptimally implemented. In order to maximize the implementation of GenRe, this study suggest to increase the knowledge and exposure of information regarding three indicators of the GenRe Program for adolescents, families who have teenage family members and communities in the territory of Indonesia, especially in East Java Province.